Misconceptions And Myths In The Management Of Animal Bite Cases - Sekhon A.S; Singh Amarjit; Kaur Paramjit; Gupta Sonia (Wolters Kluwer Medknow Publications, 2002)
Research question : What are the common myths and misconceptions in the management of animal bite cases among patients attending antirabies clinic, Rajindra Hospital Patiala. Objectives: 1. To find out beliefs and misconceptions among patients attending Antirabies clinic. 2. To study distribution of bites in relation to different variables. Setting: Antirabies clinic, Rajindra Hospital, Patiala (Deptt. of Community Medicine). Study design: Retrospective study. Sample size: 4.585 patients who attended the Antirabies clinic in a period of 3 years and 9 months. Statistical analysis: Simple proportions. Study variables : Age, sex, place, literacy, class of bite, myths. Results: Out of 4.585 patients, 71.4% were males and 61.8% reported from urban area. Majority of the patients were in age group 15-30 years and 59.2% were literate. Majority (95%) of cases were of dog bite followed by monkey bite (1.8%) buffalo bite(1.6%) and cat bit (1.3%). 38.6% patients presented with class III bites. Common practices prevalent in the management of wounds were washing with soap and water (21.02%), with only water (9.53%), application of chilies (14.18%), dettol and antiseptic (5.45%), cowdung (0.46%) and carbon (0.89%).